Diphenylethoxy-substituted metal-free and metallophthalocyanines as potential photosensitizer for photodynamic therapy: synthesis and photophysical and photochemical properties - Yilmaz, Yusuf; Erdogmus, Ali; Sener, Muhammet Kasim (Tubitak Scientific & Technological Research Council Turkey, 2014)
The synthesis of a 4-(2,2-diphenylethoxy)phthalonitrile (1) and its organosoluble free base (2), zinc(II) (3), nickel(II) (4), and cobalt(II) (5) phthalocyanine derivatives is presented in this work. The novel complexes were characterized by elemental analyses and spectral data such as infrared, nuclear magnetic resonance, ultraviolet visible, and mass data. General tendencies were described for photophysics (fluorescence) and photochemistry (photodegradation and singlet oxygen quantum yields) of the free base and zinc (II) phthalocyanine derivatives in dimethylformamide. The quantum yield values of fluorescence (Phi(F)), singlet oxygen formation (Phi(Delta)), and photodegradation (Phi(d)) for the zinc phthalocyanine were found to be 0.37, 0.48, and 9.12 x 10(-4), respectively. The photophysicochemical properties of the phthalocyanines (2 and 3) clearly reveal that these phthalocyanines could be used in singlet oxygen applications such as photodynamic therapy.
Keywords: Phthalocyanine; singlet oxygen; photodynamic therapy; fluorescence quantum yield; ZINC PHTHALOCYANINE; SOLVENTS; Chemistry; Engineering